2016
DOI: 10.7120/09627286.25.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Keel-bone damage and foot injuries in commercial laying hens in Denmark

Abstract: Keel-bone damage and foot injuries have a negative impact on welfare in laying hens. The extent of the problems in Danish commercial flocks of layers is unknown. Therefore, the aim of this study was to assess the current prevalence of keel-bone damage and foot injuries in Danish commercial flocks of laying hens and to investigate the effects of production system, housing system, hybrid and age. The occurrences of keel-bone damage, hyperkeratosis and missing toes were higher at 62 compared to 32 weeks of age, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 23 publications
1
30
1
2
Order By: Relevance
“…The animals were examined over a period of 10 months during which each animal was assessed 11 times (22,25,28,33,37,40,45,49,54,57, and 61 weeks of age). For better understanding, the term "observation Phase (P)" from 1 to 11 is used hereafter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals were examined over a period of 10 months during which each animal was assessed 11 times (22,25,28,33,37,40,45,49,54,57, and 61 weeks of age). For better understanding, the term "observation Phase (P)" from 1 to 11 is used hereafter.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, 97.0% of the animals had at least one fracture and 99.3% had at least one lesion at the end of the study (61 weeks of age). Previous studies have suggested less frequent occurrence (5,(20)(21)(22)(23)(24) with typically 50-80% of surveyed hens manifesting keel fractures by the end of lay using palpation or dissection. As a potential explanation for the relatively higher frequency seen in the current study, our protocol allowed for recent, healed, and minor fractures to be diagnosed (7,9) which could be missed with palpation and/or dissection.…”
Section: Fracture Incidencementioning
confidence: 99%
“…The barns system in Denmark consists of either single-tiered percheries or multitiered aviaries. The participating producers were originally recruited for another research project ( 17 , 33 ); 10 of the original 13 barn egg producers agreed to participate in this study. The hens were housed according to the EU regulations for barn production systems ( 34 ), i.e., the barn hens were housed at a stocking density of 9 hens/m 2 and with no outdoor access.…”
Section: Methodsmentioning
confidence: 99%
“…During all visits, a total of 100 hens were caught in different areas of the house, and the condition of plumage, skin, feet, and keel bone of each bird was assessed by trained observers ( 33 ) using the scoring protocol developed in the CORE Organic project HealthyHens ( 35 ). A sample size of 100 hens was chosen based on the recommendation of the Welfare Quality ® protocol ( 36 ) and a sample size calculation ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…During the last decade, numerous studies, done mostly in the EU countries, have documented fractures and deformation of the keel bone in laying hens, which range between 5% and 97%, depending on the housing system and hen age (Rodenburg et al, 2008;Wilkins et al, 2011;Petrik et al, 2015;Riber and Hinrichsen, 2016;Regmi et al, 2016). So far, no similar research was conducted in our country.…”
Section: Introductionmentioning
confidence: 86%